2015
DOI: 10.1002/adfm.201403763
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Tunability of Room Temperature Electronic Transport and Ferromagnetism in Dilute Magnetic Semiconductor and PMN‐PT Single‐Crystal‐Based Field Effect Transistors via Electric Charge Mediation

Abstract: Multiferroic heterostructures composed of complex oxide thin films and ferroelectric single crystals have aroused considerable interest due to the electrically switchable strain and charge elements of oxide films by the polarization reversal of ferroelectrics. Previous studies have demonstrated that the electric‐field‐control of physical properties of such heterostructures is exclusively due to the ferroelectric domain switching‐induced lattice strain effects. Here, the first successful integration of the hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 42 publications
(74 reference statements)
2
37
0
Order By: Relevance
“…Due to the nonvolatile nature of polarization charges at the interface, 35,36 the resistance for the P þ r and P À r states exhibits distinct differences down to the lowest temperature for all CBS films with different thicknesses ( Fig. 1g and Supplementary Figure S4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the nonvolatile nature of polarization charges at the interface, 35,36 the resistance for the P þ r and P À r states exhibits distinct differences down to the lowest temperature for all CBS films with different thicknesses ( Fig. 1g and Supplementary Figure S4A).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, n was modified by ∼46% at 2 K and by ∼23% at 300 K as the polarization is switched from P þ r to P À r , while the electron mobility μ is only weakly modified by the polarization switching (Supplementary Figure S4B). For the present PMN-PT with a rhombohedral crystal structure the polarization switching from P þ r (i.e., the [111] direction) to P À r (i.e., the [-1-1-1] direction), as schematically illustrated in Figure S5 (Supplementary Materials), should not induce any lattice strain, 35,36 which is confirmed by the X-ray diffraction results shown in Figure S6 (Supplementary Materials), where the PMN-PT(111) and CBS(0003), (0006), (00015) diffraction peaks remain unchanged as the polarization state was switched from P þ r to P À r . Further, PFM measurements show that the polarization direction had been fully and reversibly switched between the [111] and the [-1-1-1] directions by electric voltages, as evidenced by the uniform and sharp contrast between the two domain states within the dotted blue boxes (Fig.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that the defects in films significantly suppress the ferroelectric field effect . Since the ferroelectric field effect is an interface effect, it is expected that polarization‐switching‐induced Δρ/ρ would increase with decreasing film thickness . Such an expectation is realized in the ICO008 film whose Δρ/ρ increases from 106% for the 280 nm film to 4.3 × 10 3 % for the 17.5 nm one (Figure d).…”
Section: Resultsmentioning
confidence: 80%
“…Among all ferroelectrics reported so far, (1− x )PbMg 1/3 Nb 2/3 O 3 – x PbTiO 3 (PMN‐ x PT) single crystals are greatly favored by researchers because of their ultrahigh piezoelectric coefficient ( d 33 ≈ 2000 pC N −1 ), superior ferroelectric polarization ( P r ≈ 30–40 µC cm −2 ), ultralow leakage current (<6 nA cm −2 ), and large electromechanical coupling coefficient ( k 33 ≈ 0.9) near the morphotropic phase boundary (0.29 ≤ x ≤ 0.33) . As of now, multiple types of thin films such as vanadium dioxides, manganites, ferrites, ferromagnetic metals and alloys, semiconductors, photoluminescent oxides, and superconductors have been grown on polished PMN‐ x PT single‐crystal substrates. For all reported thin film/PMN‐ x PT heterostructures, two major effects (i.e., the lattice strain effect and the ferroelectric field effect) occur at interfacial region upon the application of electric fields to PMN‐ x PT.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on the thickness‐dependent interaction between strain‐mediated and charge‐mediated mechanisms can be found in a brief review . Recently, the strain and charge co‐mediated magnetoelectric coupling has been experimentally demonstrated in various multiferroic heterostructures, e.g., a Fe 0.5 Rh 0.5 film, a L1 0 ‐ordered FePt film, a Ni 0.79 Fe 0.21 film, a Mn‐doped ZnO film, or a Fe film epitaxially grown on PMN‐PT.…”
Section: Electrically Driven Magnetization Switching (Edms)mentioning
confidence: 99%